PROUNI: política de acesso à universidade e as diferentes leituras jurídicas da ADI 3330 - Queiroz, Rosa Maria Diekn de (Universidade do Vale do Rio dos Sinos, 2018)
The purpose of this document is to examine the University for All Program (PROUNI) through the different sociologic e legal readings presented in the 3330 / DF Direct Action of Unconstitutionality. The methodology used is the case study method, with a qualitative approach, focusing on the Direct Action of Unconstitutionality 3330 / DF, judged on May 03, 2012, by the Federal Supreme Court. In order to obtain the data, documentary sources were used, such as books, articles, theses related to the subject and access to the internet. As a result of the study it was possible to rehearse some indicators that prove to be PROUNI, while an affirmative action policy, guarantor for those who throughout the historical process were culturally excluded, could have guaranteed their rights to access and remain in higher education. Empirical data were organized into three categories: Education in Brazil; Public themes in Education; Direct Action of Unconstitutionality 3330 / DF.
Keywords: Educação superior; Prouni; Políticas públicas educacionais; Ação direta de inconstitucionalidade; Higher education; Prouni; Educational public policies; Direct action of unconstitutionality; ACCNPQ::Ciências Humanas::Sociologia